Personality aspects in the psychological analysis of the main character in thor ragnarok movie - Adnyana, I Gede Dana; Winarta, Ida Bagus Gde Nova; Resen, I Wayan (Institut Pariwisata dan Bisnis Internasional, 2020)
This thesis uses Three Aspects of Personality in Psychological, Id, Ego and Super-Ego”. This research aims to identify and explain how the main character surfaces the three aspects of personality in psychological Thor Ragnarok movie. The theory used is from Sigmund Freud theory of Psychoanalysis. Qualitative method is used to analyze the data. The researcher found the psychological dimensions of the main character, such as the id, the ego, and the superego. Thor’s id was shown in his ambition to revenge his sister who has kicked him from Asgard and disrupted life in Asgard. Thor’s ego was shown when he didn’t believe if his hammer could be destroyed because he only knows if his hammer was the strongest. Thor’s super-ego or the moral strength was shown when Thor had nightmares every night that he saw Asgard fall into ruins.